In vivo evaluation of machining forces, torque, and bone quality during skull bone grinding. (June 2020) - Babbar, Atul; Jain, Vivek; Gupta, Dheeraj
This study investigates neurosurgical bone grinding with varying parameters on skull bone using a miniature grinding burr. Three process parameters, namely, rotational speed, feed rate, and depth of cut, have been investigated at three different levels in the terms of tangential force, thrust force, and torque generated during grinding. The results revealed that as the rotational speed is increased, the cutting forces and torque showed a decreasing trend. Nevertheless, the increase in feed rate and depth of cut leads to the escalation in response characteristics. The best parametric combination for minimum cutting forces and torque is as follows: rotational speed = 55, 000 r/min, feed rate = 20 mm/min, and depth of cut = 0.50 mm. Morphological analysis reveals cracks in the bone's surface at a higher feed rate. Furthermore, delamination and cutting streaks are also visible on the surface of the bone after grinding. Energy-dispersive spectroscopy and elemental mapping of the tool after bone grinding indicate the accumulation of the bone chips in the successive diamond abrasives. The outcomes of the study will be beneficial for the neurosurgeons in understanding the effect of various process parameters on cutting force, toque, microcracks, and bone's regeneration ability during surgical bone grinding.